The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1468-3148.2007.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Feelings About Work: A Review of the Socio‐emotional Impact of Supported Employment on People with Intellectual Disabilities

Abstract: Background Work is an aspiration for many people with intellectual disability and is regarded as a vital goal by policy-makers in pursuit of social inclusion. The aim of this study was to consider the impact of supported employment on the socio-emotional well-being of people with intellectual disabilities. Method A systematic search was conducted. The review included case-controlled and longitudinal studies measuring outcomes for: (1) quality of life (QOL), (2) social life and (3) autonomy. ResultsWhile result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 48 publications
3
77
0
10
Order By: Relevance
“…Although working in the competitive workforce and living in the community tend to be associated with more relationships with non-disabled peers, these experiences seem to be more effective at increasing autonomy than they do at increasing social acceptance. 47,48 The two studies that have followed a cohort of children with ID into adulthood present a somewhat different picture. They found that approximately 3 ⁄ 4 of individuals with mild ID marry or cohabitate with a partner, but these partnerships are more likely to break-up than in the general population.…”
Section: Social Relationshipsmentioning
confidence: 97%
“…Although working in the competitive workforce and living in the community tend to be associated with more relationships with non-disabled peers, these experiences seem to be more effective at increasing autonomy than they do at increasing social acceptance. 47,48 The two studies that have followed a cohort of children with ID into adulthood present a somewhat different picture. They found that approximately 3 ⁄ 4 of individuals with mild ID marry or cohabitate with a partner, but these partnerships are more likely to break-up than in the general population.…”
Section: Social Relationshipsmentioning
confidence: 97%
“…En aquellos estudios en los que se compara la situación del empleo ordinario versus la situación del empleo protegido (Jahoda et al, 2007; Jordán de Urríes y Verdugo, 2003; se ponen de manifiesto algunas ventajas del empleo en empresas ordinarias en comparación con el trabajo en centros especiales, de tal manera que podemos concluir que el empleo ordinario, en relación al segregado, proporciona:…”
Section: Jordán De Urríes Y Verdugo 2003unclassified
“…It can also add structure and routine to one's day, increase self‐esteem and self‐perception, provide access to professional and social networks and improve quality of life (Grant ; Jahoda et al . ; Winn & Hay ). People with intellectual and developmental disabilities (IDD) have often reported the benefits of employment and most indicate being highly motivated to work (Lysaght et al .…”
Section: Introductionmentioning
confidence: 99%